2015
DOI: 10.3892/mmr.2015.4538
|View full text |Cite
|
Sign up to set email alerts
|

Smith‑Magenis syndrome in monozygotic twin fetuses presenting with discordant phenotypes and uteroplacental insufficiency

Abstract: Abstract. Smith-Magenis syndrome (SMS) is a rare condition with multiple congenital malformations caused by the haploinsufficiency of RAI1 (deletion or mutation of RAI1). However, the correlation between genotype and phenotype is not well understood. The present study describes the prenatal diagnosis of monozygotic twins with a 17p11.2 deletion, which is indicative of SMS, who presented with discordant phenotypes and uteroplacental insufficiency. A high-resolution genome-wide single nucleotide polymorphism arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Concerning the 55 MCDA twin pairs with normal karyotype, concordant pathological CNVs explaining the phenotypes were found in one twin pairs (case 75). Twin pairs of case 75 exhibited a 3.706‐Mb and a 3.672‐Mb deletion of chromosomal band 17p including the SREBF1 and RALI1 gene, which has been linked to Smith–Magenis syndrome and these two fetuses suffered with IUD at 30 gestational weeks …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Concerning the 55 MCDA twin pairs with normal karyotype, concordant pathological CNVs explaining the phenotypes were found in one twin pairs (case 75). Twin pairs of case 75 exhibited a 3.706‐Mb and a 3.672‐Mb deletion of chromosomal band 17p including the SREBF1 and RALI1 gene, which has been linked to Smith–Magenis syndrome and these two fetuses suffered with IUD at 30 gestational weeks …”
Section: Resultssupporting
confidence: 91%
“…Twin pairs of case 75 exhibited a 3.706-Mb and a 3.672-Mb deletion of chromosomal band 17p including the SREBF1 and RALI1 gene, which has been linked to Smith-Magenis syndrome and these two fetuses suffered with IUD at 30 gestational weeks. 12 In addition, CMA revealed concordant unclear significance CNVs in two twin pairs of the cytogenetically normal fetuses (case 142 and case 110). Case 142 exhibited a small (521 Kb) microduplication in 15q11.2 including the CYFIP1 gene in both twins; we concluded that the duplication was not responsible for the phenotype of the fetus.…”
Section: Resultsmentioning
confidence: 94%
“…Additionally, it is possible that the cause of these congenital malformations may not be directly related to genetics and may involve a currently unidentified environmental factor. 23 Case 23 had a 205-Kb deletion in chromosome 16p13.3 detected by postnatal CMA that was linked to Rubinstein-Taybi syndrome, a condition characterized by short stature, moderate-to-severe intellectual disability, distinctive facial features, and broad thumbs and first toes. 24,25 Additional features of this disorder can include eye abnormalities, heart and kidney defects, dental problems, and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of fetuses with pathogenic CNVs (cases[22][23][24][25][26][27] or VOUS (cases 28-30) detected by CMA among the 52 fetuses with VSDs with normal karyotypes DA, ductus arteriosus; DORV, double outlet right ventricle; FGR, fetal growth restriction; IAA, interruption of aortic arch; PDA, patent ductus arteriosus; PS, pulmonary artery stenosis; SUA, single umbilical artery; TOP, termination of pregnancy; UCB, umbilical cord blood.…”
mentioning
confidence: 99%
“…It is worth noting that the major features that are considered central to the diagnosis of TP63 ‐related disorder were discordant, while features that are minor (e.g., volar nail sign, complexion) or less common (e.g., choanal atresia, T‐cell lymphopenia) were concordant. While this is the first report of discordant major malformations but concordant minor and less common malformations in monozygotic twins with TP63 ‐related disorders, there are many other examples in the literature of discordant anomalies in monozygotic twins with genetic syndromes (Burgemeister et al, ; McDonald‐McGinn et al, ; Votava‐Smith, Pitukcheewanont, Randolph & Chmait, ; Zhou et al, ).…”
Section: Discussionmentioning
confidence: 86%